2007
DOI: 10.1007/s10853-006-1229-7
|View full text |Cite
|
Sign up to set email alerts
|

Deformation defects in nanocrystalline nickel

Abstract: Defects induced by plastic deformation in electrodeposited, fully dense nanocrystalline (nc) Ni with an average grain size of 25 nm have been characterized by means of high resolution transmission electron microscopy. The nc Ni was deformed under uniaxial tension at liquid-nitrogen temperature. Trapped full dislocations were observed in the grain interior and near the grain boundaries. In particular, these dislocations preferred to exist in the form of dipoles. Deformation twinning was confirmed in nc grains a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…This could sometimes lead to serious problems because it is known that grain sizes affect the deformation mechanisms [24,37,57,59,171,185]. For example, it was observed by MD simulations that nc Al, Cu and Ni rarely deform by twinning [10], which contradicts the experimental observations [2,6,23,[33][34][35]66,68,77,[186][187][188][189]. This controversy was later found caused by the grain size effect, i.e.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…This could sometimes lead to serious problems because it is known that grain sizes affect the deformation mechanisms [24,37,57,59,171,185]. For example, it was observed by MD simulations that nc Al, Cu and Ni rarely deform by twinning [10], which contradicts the experimental observations [2,6,23,[33][34][35]66,68,77,[186][187][188][189]. This controversy was later found caused by the grain size effect, i.e.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%
“…However, in nc fcc metals, multiple twins often form, which show no obvious plate-like morphology (see Fig. 5b) [34,42,56,[65][66][67][68][69][70]. Under such circumstances, HREM is needed to identify and study the deformation twins.…”
Section: Basics Of Deformation Twinning In Fcc Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among such metals, copper, nickel and aluminum have been the most extensively studied [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. For those fcc metals, a grain size as small as 10 nm can be produced by various techniques.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally thought that FCC metals with grain size 50-100 nm deform predominantly via the slip of lattice dislocations, and for grains larger than 100nm they deform exclusively through this mechanism [ 10 ]. Various works have shown that in nanostructured materials (grain size < 50 nm) alternative deformation mechanisms involving deformation twins [11,12,13], and stacking faults (SFs) [14,15] can occur. In some cases these types of defects have even been observed in grains with size up to 100 nm [12], but it is not evident that they make a significant contribution to deformation in these SPD processed materials.…”
Section: Introductionmentioning
confidence: 99%